Intelektual Muslim Baru yang Menetas Semasa Orde Baru - Nanang Tahqiq (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 1999)
The main thesis of this book is that during the New Order era, a unique and distinct Islamic intellectual movement emerged, known as Neo-Modernism. Nurcholish Madjid, Djohan Effendi, the late Ah. Mad Wahib, and Abdurrahman Wahid are four figures of this Neo-Modernist movement. The hallmark of their intellectual movement lies in their mastery of classical/traditional Islamic knowledge (commonly referred to as